Fundamentals of Management science - Turban, Efraim; Meredith, Jack R. (Boston Richard D.Irwin, INC, 1991)
New edition of a standard text first published in 1977. It emphasizes a scientific approach to decision making.
Donated by: Anvar Hodjaev